The Quality of Health and Education Systems Across Africa : Evidence from a Decade of Service Delivery Indicators Surveys - Gatti, Roberta (Washington, DC: World Bank, 2021)
Have teachers mastered the subject matter they are teaching? Can doctors accurately diagnose and treat critical health conditions? Are schools and health facilities sufficiently stocked with needed equipment and supplies? Are they sufficiently supported and staffed to optimize learning and health care outcomes? For the past decade, the World Bank’s Service Delivery Indicators (SDI) surveys have collected nationally representative data in countries across Africa to answer these questions. The surveys aim to measure the quality of services where they meet citizens: in schools and health facilities. The Quality of Health and Education Systems Across Africa: Evidence from a Decade of Service Delivery Indicators Surveys identifies areas of achievement and constraint in service delivery, shedding light on how service delivery may foster or stunt human capital accumulation. SDI surveys show that schools and health clinics across Africa are still falling short in some critical areas. The delivery of primary care services is very heterogenous between and within countries. Many health facilities lack the basic necessities to provide proper care, such as essential medicines, basic diagnostic equipment, and adequate water and sanitation. Moreover, health care providers’ ability to diagnose and treat common health conditions correctly is low and distributed unevenly. Health personnel’s absence from health facilities remains a concern across the surveyed countries. Learning is low, and, not unlike health care, levels of student learning vary significantly across countries: less than half of grade 4 students can recite a simple sentence or perform basic mathematical operations. This deficient learning is correlated with teachers’ low levels of content knowledge and sub-par pedagogy skills. Some schools are also missing crucial inputs, such as blackboards or private and gendered toilets, and struggle with high pupil-teacher ratios. Despite these challenges, success stories in both sectors illustrate the quality of service delivery that could be achieved and showcase the dedication of teachers and medical staff across Africa. By studying data from thousands of facilities, considering the local context, and drawing insights from the literature, this book offers important insights for how countries can strengthen health and education systems and build back better in the wake of the massive disruptions brought about by the COVID-19 pandemic.